Implication of Disulfide Bridge Induced Thermal Reversibility, Structural and Functional Stability for Luciferase - Naderi, Mina; A. Moosavi-Movahedi, Ali; Hosseinkhani, Saman; Nazari, Mahboobeh; Bohlooli, Mousa; Hong, Jun; Hadi-Alijanvand, Hamid; Sheibani, Nader (Protein and Peptide Letters, 2015)
Firefly luciferase is a relatively unstable protein and commonly loses its activity at room temperature because of structural changes. The structural and functional stability of this protein is critical for its enzymatic applications. Different approaches are applied to increase the stability of this enzyme such as designing of covalent cross-links (disulfide bonds). In this study, luciferase mutants containing one or two disulfide bonds were compared to the native protein for their fortheir structural, thermodynamic, and functional properties. Mutant forms of P. Pyralis luciferase A296C-A326C and A296C-A326C/P451C-V469C were used. Thermodynamic and biophysical studies were carried out using UV-Vis, fluorescence, circular dichroism, luminescence spectroscopy and differential scanning calorimetry (DSC). We observed that both mutant forms of the protein were more stable than the wild-type enzyme. However, the single disulfide bond containing mutant was structurally and functionally more stable than the mutant protein containing two disulfide bonds. Furthermore, the enzymatic activity of the single disulfide bond containing mutant protein was 7-folds greater than the wild type and the double disulfide bond proteins. The A296C-A326C mutation also increased the reversibility and disaggregation of the protein. The enhanced activity of the single disulfide bond mutant protein was contributed to the expansion of its active site cleft, which was confirmed by bioinformatics tools.
Keywords: disulfide bridge mutants